Developing an Islamic Educational Environment for Elementary School/Madrasah Ibtidaiyah - Age Children - Mizani, Hilmi; Ramli, M. (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The educational environment can be in the form of physical or psychological, which is related to the life of the child, including the family, school and community environment, which must be fostered in a conducively, to make noble educational goals. This study aims to show the development of an educational environment with Islāmic nuances for common or Islāmic elementary school children. For this reason, this research a type library research, whose data sources are taken from the texts of the Qur’an and al-Hadith, books, and journals about Islamic education. While the data analysis used descriptive qualitative analysis. The results of this study illustrate that fostering an Islāmic educational environment for common or Islāmic elementary school children in the family environment must cultivate an Islāmic life, starting from eating, drinking, talking, dressing, decorating the house, using social media and others. At school, an Islāmic atmosphere is created, there is a prayer room, congregational prayers, Ramadan Islāmic boarding schools, reading Qur'an, congregational Zuhr prayers, donations for orphans, Friday alms, and commemoration of Islāmic holidays. In the community, mosques were built with congregational prayers, Friday prayers, tarawih prayers, eclipse prayers, Qur'an education, learning together with Shaikh, receiving and distributing Zakat, and commemorating major Islāmic holidays, and the community also maintained morals of children, thus causing disobedience